The Effect of Accounting Earnings, Total Cash Flow, and Net Profit Margin on Stock Returns: Evidence from Infrastructure Companies Listed on the Indonesia Stock Exchange (2021–2024) - Tasya Putri Abidtya; Fitria Magdalena Suprapto; Rike Selviasari (LP2M IAIN Palopo, 2026)
Stock return is one of the important indicators used by investors to assess the success of their investments in the capital market. Changes in stock returns are influenced by various factors, both from the company's financial performance and external conditions. This study aims to analyze the effect of accounting profit, total cash flow, and net profit margin on stock returns of infrastructure sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research employed a quantitative approach using secondary data obtained from companies’ annual financial reports and stock price data. The sampling technique used was purposive sampling, resulting in 25 companies with a total of 100 research observations. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination with the assistance of IBM SPSS Statistics software. The results indicate that accounting profit has a negative and significant effect on stock returns, total cash flow has no significant effect on stock returns, while net profit margin has a positive and significant effect on stock returns. Simultaneously, accounting profit, total cash flow, and net profit margin significantly affect stock returns. The coefficient of determination value of 11.1% indicates that the ability of the three independent variables to explain variations in stock returns is relatively limited, while the remaining 88.9% is influenced by other factors outside the research model. The findings imply that corporate profitability information, particularly net profit margin, can be considered by investors in making investment decisions within the infrastructure sector and may serve as a reference for future studies regarding factors affecting stock returns.